Diabetes mellitus does not negatively impact outcomes and satisfaction following unicompartmental knee arthroplasty in well-controlled disease - Gin Way Law (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2019)
Background: Unicompartmental knee arthroplasty (UKA) has gained popularity in recent years in view of its minimally invasive nature and proven benefits over the traditional total knee arthroplasty (TKA) in terms of superior knee range of motion and kinametics, faster recovery, lower blood loss, shorter hospital stay and ease of revision with the preservation of bone stock.With the increasing incidence of diabetes mellitus (DM) worldwide and an increased risk of deep infection, wound complications and early failure previously shown in diabetic patients undergoing TKA, it is prudent that we establish the impact of DM on the outcomes and complications of UKA given that there is little on the topic in the current literature.This is especially significant in Asia as Asia is home to more than 60% of the world's population of diabetic patients with estimates of more than 200 million people having the condition. Type 2 DM in particular, is an increasing epidemic with projections to increase by more than 150% between year 2000 and 2035.The purpose of this study is to evaluate the impact of diabetes mellitus on the outcomes and satisfaction of UKA at 2 years postoperatively. We hypothesize that diabetes mellitus does not affect the outcomes and satisfaction following UKA in Asians at 2 years postoperatively. Methods: We conducted a retrospective review of prospectively collected registry data of 1075 UKAs performed in a multiethnic Asian population between 2006 and 2013 at our institution. Outcomes assessed included flexion range, Knee Society Score (KSS), Oxford Knee Score (OKS), Short-Form 36 (SF-36) and satisfaction scores.All patients with DM were identified and matched with patients without DM for age, gender and body mass index. Outcomes, satisfaction, complication and revision rates were then compared between the two groups up to 2 years postoperatively. Preoperative HbA1c was used to assess the patients’ blood glucose control in the DM group. Results: A total of 104 patients (9.7%) had DM, close to the national prevalence (11.3%). At 2 years postoperatively, DM patients had better improvement in their SF-36 Mental Component Score (MCS) (p = 0.015) despite poorer preoperative scores (DM group = 70 ± 23, non-DM group = 77 ± 17, p = 0.013), and were in 1° more varus (p = 0.005) when compared to patients without DM.There was no significant difference in the proportion of patients achieving the minimal clinically important difference for knee-specific outcomes (DM:90%, non-DM:96%) or the satisfaction rates between the groups (DM:92%, non-DM:94%). Complication rates were similar (DM:5.8%, non-DM:4.8%). There were no venous thromboembolic events, deaths or revisions during the follow-up period in both groups. The mean preoperative HbA1c in our DM group was 6.6%. Conclusion: In this matched-pair study of diabetic versus non-diabetic patients undergoing surgery for UKA, DM does not have a clinically significant negative impact on the outcomes and satisfaction following UKA in patients with well-controlled disease. Keywords: Unicompartmental knee arthroplasty, UKA, Diabetes mellitus, Outcomes, Satisfaction